Lean service model with Simulation in Arena to improve response time of the technical service in a Peruvian SME - Espinoza Guzmán, Renato Gregorio (2023)
The services sector has maintained sustained growth in recent decades, becoming one of the sectors contributing most to the global economy. However, the characteristics of these activities represent a challenge to companies in the sector, which seek to be more competitive in the presence of new technologies and a globalized world. In this context, the companies that offer field service for the maintenance of machinery and equipment present problems in planning their activities due to the uncertainty in demand, the distances to be covered, and to comply with the expected response time of the client. Therefore, to solve these problems, this article proposes applying manpower planning strategies and lean tools to reduce the response time in field service. The simulation models are based on these strategies and were structured and validated using Arena simulator. A 7% improvement in service level was obtained, considering the contractual response time offered to customers. The proposal will provide alternatives for field service planning and provide companies with tools to increase their competitiveness.